2021
DOI: 10.1002/gcc.23011
|View full text |Cite
|
Sign up to set email alerts
|

Survey of germline variants in cancer‐associated genes in young adults with colorectal cancer

Abstract: Colorectal cancer (CRC) incidence in young adults is rising. Identifying genetic risk factors is fundamental for the clinical management of patients and their families. This study aimed to identify clinically significant germline variants among young adults with CRC. Whole‐exome sequencing data of blood‐derived DNA from 133 unrelated young CRC patients (<55 years of age) underwent a comprehensive analysis of 133 cancer‐predisposition/implicated genes. All patient tumors were evaluated for mismatch repair defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Almost all of these 25 variants were in known DNA repair genes such as MLH1, MSH2, MSH6, MUTYH, ATM and BRCA2. However, 2 of the 25 variants were found in CFTR [ 41 ]. Another recent study identified 14 polymorphic variants involved in familial predisposition to serrated polyposis syndrome, a condition in which colorectal polyps are highly susceptible to progression to adenocarcinomas.…”
Section: Involvement Of Cftr In Gi Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all of these 25 variants were in known DNA repair genes such as MLH1, MSH2, MSH6, MUTYH, ATM and BRCA2. However, 2 of the 25 variants were found in CFTR [ 41 ]. Another recent study identified 14 polymorphic variants involved in familial predisposition to serrated polyposis syndrome, a condition in which colorectal polyps are highly susceptible to progression to adenocarcinomas.…”
Section: Involvement Of Cftr In Gi Cancersmentioning
confidence: 99%
“…Germline heterozygous carriers of specific CFTR polymorphic variants are also at a higher risk for CRC, including in young adults [ 41 ] and in patients with familial serrated polyposis syndrome [ 42 ].…”
Section: Figurementioning
confidence: 99%
“…As summarized in Table 1 , among 22 FANC genes, FANCS/BRCA1 and FANCD2/BRCA2 , high-risk hereditary breast-ovarian cancer syndrome susceptibility genes, are the most investigated as CRC susceptibility genes beyond its well-known predispositions [ 27 , 28 , 29 , 30 , 31 , 44 , 73 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Recent findings revealed that the prevalence of BRCA1/2 PVs among early-onset (1.3%) [ 30 ] and unselected patients with CRC (3.9%) [ 88 ] is more frequent than would be happening by chance.…”
Section: Potential Role Of Fanc Gene Mutations In ...mentioning
confidence: 99%
“…Nonetheless, it must be noted that, among the available studies, there are significant variations in the ratio of patients harboring even the same mutation. This occurrence might be due to the various methodological approaches used (e.g., PCR, arrays, different NGS platforms) and the consequent number of genes analyzed (e.g., candidate mutation screenings, panels including a variable number of genes, whole-exome sequencing) as well as to ethnic differences since several studies include mainly European populations [ 27 , 28 , 30 , 31 , 72 , 73 , 83 , 85 , 86 , 87 , 88 , 89 , 96 ], whereas some others considered Asian populations [ 29 , 44 , 84 ]. A summary of the associations between germline variations in FANC genes and CRC is presented in Table 1 .…”
Section: Potential Role Of Fanc Gene Mutations In ...mentioning
confidence: 99%
“…In endometrial cancer, BRIP1 correlated to tumor recurrence and patients with mutations in BRIP1 might beneft from poly ADP-ribose polymerase (PARP) inhibitors [7]. Mikaeel et al reported that BRIP1 might be a cancerpredisposing gene in young-onset colorectal cancer [8]. Mani et al suggested that BRIP1 was of the imperative role in maintaining neuronal cell health and homeostasis by suppressing oxidative stress, excitotoxicity induced DNA damage, and protecting mitochondrial integrity [3].…”
Section: Introductionmentioning
confidence: 99%